The constellation of Lacan’s subject register in Damar Shashangka’s translation of Serat Gatholoco - Yostiani Noor Asmi Harini; Hegar Krisna Cambara (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2022)
The constellation of Lacan’s subject register in Damar Shashangka’s translation of Serat GatholocoGatholoco is a figure in Serat Gatholoco, a literary work suspected to be written in the early 19th century. The Gatholoco character is said to have a constellation of desires that presents subversive symptoms, positioning Serat Gatholoco as a controversial text at that time. The aim of this study is to describe the constellation of desires in Serat Gatholoco translation from Damar Shashangka, using the economics perspective of the Lacanian subject. This study used the qualitative interpretive method. The result shows Gatholoco as a sublimation of ideas that become the image-subject in the symbolic register, which is a manifestation of alienation symptoms suppressed in the discourse of the Ruler. Naming as a true-born man declared by Gatholoco is a form of active narcissistic desire, a metonymy that connects identification and desire for Gatholoco’s self-hood. The identity of the naming is the substitution of one marker with the Other. Its word is a paternal metaphor, the substitution of the Father’s name (resistance efforts) for the Mother’s desire (primordial existence). This metaphor offers substantial resistance to the Father’s Law (puritan existence). In the end, the nicknames of Gatholoco are a form of the narcissistic desire of the author.Keywords: Gatholoco, a constellation of desires, psychoanalysisKonstelasi subjek register Lacanian dalam Serat Gatholoco terjemahan Damar ShashangkaGatholoco ialah tokoh yang terdapat dalam Serat Gatholoco yang diperkirakan ditulis pada awal abad ke-19. Tokoh Gatholoco dikisahkan memiliki konstelasi hasrat yang menyajikan gejala subversif sehingga Serat Gatholoco menjadi teks yang kontroversial pada zamannya. Tulisan ini bertujuan mendeskripsikan konstelasi hasrat dalam Serat Gatholoco terjemahan Damar Shashangka ditilik dari ekonomi subjek register Lacanian. Metode kualitatif interpretatif digunakan dalam penelitian ini. Hasil penelitian menunjukkan Gatholoco sebagai sublimasi gagasan yang menjadi citra-subjek dalam register simbolik yang merupakan manifestasi gejala alienasi yang ditekan dalam diskursus Sang Penguasa. Penamaan seperti lelaki sejati yang dideklarasikan Gatholoco merupakan bentuk hasrat narsistik aktif, metonimia yang menghubungkan identifikasi dan hasrat atas kedirian Gatholoco. Identitas atas penamaan tersebut merupakan substitusi satu penanda dengan Liyan. Kata tersebut merupakan metafora yang bersifat paternal, substitusi nama Ayah (upaya resistensi) demi hasrat sang Ibu (eksistensi primordialitas). Metafora tersebut menawarkan perlawanan secara subtansial terhadap Hukum Sang-Ayah (eksistensi puritan). Pada akhirnya, nama-nama sebutan dari identitas Gatholoco merupakan bentuk hasrat narsistik  pengarang serat itu sendiri.Kata kunci: Gatholoco, konstelasi hasrat, psikoanalisis